Jerónimo!: Innovation in the teaching of Marketing in higher education (National Administration Journal, 2025)
This article presents the innovative experience of the ¡Jerónimo! program, a transversal strategy developed at the Centro Universitario de los Altos (University of Guadalajara) to enrich the teaching of Marketing and strengthen the comprehensive education of students. Inspired by symbols of courage and academic references in marketing, the program integrates conferences, academic competitions, student-led journals, creative festivals, and scientific dissemination activities, aiming to transform learning into meaningful and socially relevant experiences.The initiative is distinguished by its student-driven nature, with faculty serving as advisors, fostering autonomy, leadership, and teamwork. It also incorporates cultural, artistic, sports, and social responsibility dimensions that enable students to develop essential soft and professional skills for their future careers. Among the most significant results are increased student motivation, high-impact academic production —including publications in international media— and the consolidation of a strong sense of university identity.The ¡Jerónimo! program demonstrates that educational innovation in university-level marketing can transcend the classroom to become a catalyst for creativity, social engagement, and academic excellence, offering a replicable model for other higher education institutions.
Keywords: Higher education; educational innovation; marketing; professional competencies; extracurricular activities